Effect of land configuration methods and planting depth on growth and flowering of gladiolus (Gladiolus spp.) - DODIYA, TRUPTI; THUMAR, B. V.; SAVALIYA, V. M.; BHUVA, S. K. (Journal of Ornamental Horticulture, 2025)
The present experiment was carried out at department of Floriculture and Landscape Architecture, College of Horticulture, Junagadh Agricultural University, Junagadh (Gujarat) during the years 2021-22 and 2022-23 with randomized block design (Factorial) having three replications. The treatment combinations consisting three land configuration methods (L1- Flat bed, L2- Raised bed with 2 rows and L3- Ridge and furrow) and two planting depth (D1- 3.5 cm and D2- 5.5 cm). The results indicated that minimum days taken to sprouting (8.00), days required for first spike emergence (72.25 days), maximum sprouting percentage at 15 days (74.41%), sprouting percentage at 20 days (85.62%), plant height (55.58 cm), number of leaves per plant (6.84), length of spike (43.66 cm), number of florets per spike (8.33), length of rachis per spike (28.92 cm), number of spikes per plant (1.61), yield of spikes per hectare (1.80 lakh) and vase life of spikes (13.93 days) were recorded with raised bed with 2 rows (L2). The variation due to planting depth was also found significant for all the parameters except plant height, length of rachis per spike and vase life of spikes. Minimum days taken to sprouting (8.11), days required for first spike emergence (74.32%), maximum sprouting percentage at 15 days (73.80%) and sprouting percentage at 20 days (84.55%), number of leaves per plant (6.74), length of spike (35.48 cm), number of florets per spike (7.76), number of spikes per plant (1.48), yield of spikes per hectare (1.65 lakh) were obtained with planting at 3.5 cm depth (D1). Raised bed planting had favourable effects on growth and flowering of gladiolus as compared to ridge and furrow and flat bed planting. Gladiolus plants with better growth and flowering parameters can be obtained from planting on raised bed with 2 rows (L2) at 3.5 cm (D1) planting depth.